Exploring Opportunities and Challenges of Entrepreneurship in Algeria’s Media Industry: Insights from Media and Communication Faculty Members at Algerian Universities - Djamel, Boudra; Mounir, Ayadi (Journal of Ecohumanism, 2026)
The study aimed to analyze the challenges and opportunities facing entrepreneurship in the media industry in Algeria, based on the views of 44 media professors. The results showed that the main challenges include difficulty in securing funding, lack of financial sustainability, and intellectual property protection. The study also highlighted that changes in media content consumption patterns present opportunities for developing innovative projects that meet the needs of the audience. There is a clear need for strategies to support funding, enhance cybersecurity, and encourage innovation to ensure sustainability in the sector.